Study on the driving factors of watershed runoff change in Zuli River by Budyko hypothesis and soil and water assessment tool model - Yun Zhao; Rui Zhang; Heping Shu; Yaxian Li; Zhi Xu; Qiang Wang (Ecological Indicators)
The Loess Plateau Basin faces challenges, such as soil erosion, vegetation restoration pressure, and ecological security. By identifying the driving factors of runoff changes, specific actions aimed at conserving soil and water, along with strategies for managing water resources, can be implemented. Therefore, the Zuli River was selected as the study site. The Mann-Kendall and Pettitt test methods were applied to analyze the mutation annual change and evolution of runoff from 1957 to 2022, the elasticity theory was applied to conduct sensitivity analysis on land use types, and the soil and water assessment tool (SWAT) model and Budyko hypothetical theory were utilized to quantitatively assess the driving factors behind runoff change. The results indicate that the annual runoff of Huining, Guochengyi, and Jingyuan decreased at rates of −0.03 × 108, −0.06 × 108 and −0.15 × 108 m3·(10a)-1, respectively. The sensitivity of land use to runoff changes was the most pronounced from 2000 to 2020, the land use categories most sensitive were grassland, cultivated land, forest land, and building land. The primary factor contributing to decrease in runoff was human activities, and the verification and rate of SWAT models are regularly acceptable. The contribution rate of human activities to HN, GCY and JY was 58 %, 65 % and 44 % by the Budyko hypothesis, and the precipitation was 28 %, 26 % and 23 %, respectively. The contribution rate of human activities to HN, GCY and JY was 63 %, 73 % and 68 %, and the climate change was 38 %, 27 % and 32 % by SWAT model, the percentage of runoff change attributed to land use were 45 %, 41 %, and 67 %. Therefore, the significance of human activities must be taken into account in ecological protection and water-related initiatives within the Loess Plateau gully region, so as to formulate effective sustainable development strategies for the future integrated management of the basin.